Inhibitory activity of high antioxidant Australian native fruits against the bacterial triggers of selected autoimmune diseases - Cock, I.E.; Maen, A. (Pharmacognosy Communications)
High antioxidant capacities have been linked to the treatment of rheumatic diseases and in the inhibition of microbial growth. Recent reports have identified several native Australian fruits with high antioxidant capacities. Despite this, several of these species are yet to be tested for the ability to inhibit the growth of the bacterial triggers of autoimmune inflammatory diseases. Methods: Solvent extracts prepared from selectedAustralian native fruits were analysed for antioxidant capacity by the DPPH free radical scavenging assay. Growth inhibitory activities against bacterial species associated with initiating rheumatoid arthritis and ankylosing spondylitiswere determined bydisc diffusion assay and quantified by MIC determination. Toxicity was determined by Artemia franciscana bioassay. Results: Methanolic extracts of all plant species displayed high antioxidant contents (equivalent to approximately 7-16 mg of vitamin C per gram of fruit extracted). Most aqueous extracts also contained relatively high antioxidant capacities. In contrast, the ethyl acetate, chloroform and hexane extracts for most species (except lemon aspen and bush tomato) had lower antioxidant contents (below 1.5 mg of vitamin C equivalents per gram of plant material extracted). Interestingly, the bacterial growth inhibitory activity of the extracts did not correlate with their antioxidant capacities. The fruit extracts with the highest antioxidant capacities (lemon aspen and desert lime methanolic extracts) had only low antibacterial activity, with MIC values generally >10,000 µg/ml against all bacterial species. In contrast, the Illawarra plum and desert lime ethyl acetate extracts, which had mid-range antioxidant capacities (1-6.5 mg ascorbic acid equivalents/g extracted), had potent bacterial growth inhibitory activity (200-400 µg/ml). The native tamarind ethyl acetate extract displayed low-moderate toxicity in the Artemia franciscana bioassay (LC50valuesbelow 1000 µg/mL).All other extracts were nontoxic. Conclusion: The lack of toxicity and inhibitory activity against microbial triggers of rheumatoid arthritis and ankylosing spondylitis by the fruit extracts indicates their potential in the treatment and prevention of these diseases.
Keywords: Muntries; Illawarra plum; lemon aspen; native tamarind; desert lime; bush tomato; rheumatoid arthritis; ankylosing spondylitis